Severe coronavirus disease 2019 pulmonary disease in very low birth weight preterm babies - Randad, Kailas; Bishnoi, Deepika; Sakhare, Swati; Jethaliya, Rahul (Indian Journal of Child Health, 2021)
Severe coronavirus disease 2019 (COVID-19) in neonates is considered a rarity due to vertical transmission and most of the affected babies are asymptomatic. Here, we describe two severe cases of very low birth weight (VLBW) preterm babies in sick newborn care unit (SNCU) due to horizontal transmission. Case 1 describes a VLBW preterm baby (29 weeks) weighing 1300 g who was undergoing care in SNCU. He developed classical symptoms of cold in the form of nasal congestion with mild rhinorrhea, fever, and cough followed by severe prolonged hypoxia with full recovery. Case 2 describes another VLBW preterm (27.3 weeks) weighing 1175 g who was suffering from severe progressive hypoxia around same time. He was initially responsive to oxygen therapy but succumbed to refractory hypoxia later on. We conclude that severe COVID-19 pulmonary disease can occur in few unfortunate VLBW preterm neonates